Selecting children for head CT following head injury. Issue 10 (22nd July 2016) - Kemp, A; Nickerson, E; Trefan, L; Houston, R; Hyde, P; Pearson, G; Edwards, R; Parslow, RC; Maconochie, I
Abstract : Objective: Indicators for head CT scan defined by the 2007 National Institute for Health and Care Excellence (NICE) guidelines were analysed to identify CT uptake, influential variables and yield. Design: Cross-sectional study. Setting: Hospital inpatient units: England, Wales, Northern Ireland and the Channel Islands. Patients: Children (<15 years) admitted to hospital for more than 4 h following a head injury (September 2009 to February 2010). Interventions: CT scan. Main outcome measures: Number of children who had CT, extent to which NICE guidelines were followed and diagnostic yield. Results: Data on 5700 children were returned by 90% of eligible hospitals, 84% of whom were admitted to a general hospital. CT scans were performed on 30.4% of children (1734), with a higher diagnostic yield in infants (56.5% (144/255)) than children aged 1 to 14 years (26.5% (391/1476)). Overall, only 40.4% (984 of 2437 children) fulfilling at least one of the four NICE criteria for CT actually underwent one. These children were much less likely to receive CT if admitted to a general hospital than to a specialist centre (OR 0.52 (95% CI 0.45 to 0.59)); there was considerable variation between healthcare regions. When indicated, children >3 years were much more likely to have CT than those <3 years (OR 2.35 (95% CI 2.08 to 2.65)). Conclusion: Compliance with guidelines and diagnostic yield was variable across age groups, the type of hospital and region where children were admitted. With this pattern of clinical practice the risks of both missing intracranial injury and overuse of CT are considerable.